Observed and effective number of alleles on commercial kampung chickens in Peninsular Malaysia - Ismail Affendee, Azlina Azma; Panandam, Jothi Malar (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2018)
One hundred eighty birds from three commercial kampung chicken farms and 1 commercial broiler farm were analysed to measure their genetic relationship between each population using 27 microsatellite markers. Only 24 microsatellites are polymorphic with 2 to 9 alleles. The mean number of alleles per locus in KCA, KCB, KCC and CBR was 5, 5, 3 and 5 respectively. The effective number of alleles varied from 1.06 to 5.15 KCA, 1.06 to 5.88 KCB, 1.29 to 6.88 in KCC and 1.18 to 5.17 in CBR.